Diplomasi Budaya dan Konservasi Laut di Coral Triangle Untuk Membangun Jembatan Kerjasama Regional - Zahra Dwi Wardhania; Agussalim Burhanuddin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The Coral Triangle, situated in the western Pacific Ocean, is famous for its exceptional natural wealth and abundant coral reefs, earning it the title of the